Sistematični pregled učinkovitosti statinov pri zmanjševanju vrednosti holesterola LDL - Kos, Mitja (Farmacevtski vestnik, 2007)
The aim of the analysis is an up-to-date systematic review of statin efficacy in reduction of LDL cholesterol values. MethodsČ Systematic review of statin efficacy was based on the review of all meta-analyses and individual randomized controlled clinical studies that were published recently and therefore not being included in one of the meta-analysis. The search of literature was done in Medline. ResultsČ Statins differ in regards to their efficacy. Pravastatin, 10 mg had the lowest efficacy and on average a 29 percent reduction of LDL cholesterol. Rosuvastatin, 40 mg had the highest efficacy and on average a 55 percent reduction of LDL cholesterol
Keywords: efficiency; holesterol; statini; učinkovitost